2022
DOI: 10.1016/j.applthermaleng.2021.117844
|View full text |Cite
|
Sign up to set email alerts
|

A detailed energy analysis of a novel evaporator with latent thermal energy storage ability

Abstract: The direct integration of phase change materials (PCM) into refrigeration and air conditioning systems through compact modules is an identified literature gap. In response to the literature gap, this paper provides a detailed energy analysis of a novel compact thermal energy storage module, that allows its direct integration into a refrigeration system as the evaporator. The study addresses key aspects of thermal energy storage (TES) and heat transfer mechanism that complement the previous analyses of the nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…where the sub-index i refers to each of the volume elements, n = 9 is the total number of volume elements considered (equal to the number of PCM temperature sensors), m PCM,i is the mass of PCM, m HTF,i is the mass of HTF, and m Al,i is the mass of aluminium in volume element i, a sub-index t refers to the time instant, with t ch being the time taken to complete the charging process. The enthalpy or the specific heat capacity, the measured temperature and the mass of each material were incorporated into the finite element method detailed in [15,28] to obtain the energy level in the module. Thereafter, basic equations of thermodynamics {Equations (3)-( 9)} on heat transfer and energy balance adapted from [29] were used to complete the evaluation.…”
Section: Theoretical Evaluation Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…where the sub-index i refers to each of the volume elements, n = 9 is the total number of volume elements considered (equal to the number of PCM temperature sensors), m PCM,i is the mass of PCM, m HTF,i is the mass of HTF, and m Al,i is the mass of aluminium in volume element i, a sub-index t refers to the time instant, with t ch being the time taken to complete the charging process. The enthalpy or the specific heat capacity, the measured temperature and the mass of each material were incorporated into the finite element method detailed in [15,28] to obtain the energy level in the module. Thereafter, basic equations of thermodynamics {Equations (3)-( 9)} on heat transfer and energy balance adapted from [29] were used to complete the evaluation.…”
Section: Theoretical Evaluation Methodologymentioning
confidence: 99%
“…To obtain the PCM enthalpy and specific heat capacity over a wider range of temperature, experiments were carried out using DSC 3+ Toledo equipment with 0.1 K precision for temperature and 3 J•s −1 for enthalpy. The results obtained from the DSC measurements were reported in [25] and used to generate the PCM enthalpy curve ℎ (in kJ•kg −1 ) as a function of its temperature 𝑇 (in °C), as shown in Equation (1) [15]. For the comparison of the three modules, experiments were performed for three operating modes, i.e., charging mode, discharging mode, and three-fluids HEX mode.…”
Section: Materials and Its Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In numerical studies reporting internal energy as a function of time is commonly done although most studies report latent stored internal energy (e.g., [71,99,104,130]) or total liquid fraction (e.g., [65, 66, 68, 70, 71, 75, 77, 93, 99, 102, 104, 106, 109, 111, 113, 115, 120-122, 124-128, 130-132, 134, 136]) instead of total stored energy (e.g., [75,111,115,134,137,138]). In experimental studies, the total liquid fraction is sometimes reported (e.g., [67,87,101]) however local temperature measurements are far more commonly reported (e.g., [63,64,69,72,76,83,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][105][106][107][108][109][110][111][112][113]…”
Section: State Indicatorsmentioning
confidence: 99%